2005
DOI: 10.1007/11574620_58
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Service Integration for Water Resource Management

Abstract: Water resource management is becoming increasingly difficult due to the interaction of conflicting factors such as environmental sustainability and economic constraints. In Australia, the introduction of a water rights management framework is an administrative attempt to facilitate the resolution of this complex and multi-faceted problem. Policies relating to water allocation and trading have already advanced beyond our abilities to monitor, measure, report and enforce these policies. Mismanagement of this val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
(14 reference statements)
0
10
0
1
Order By: Relevance
“…One can mention references in (Ackland et al 2005) where an Australian Web-based service is suggested whose role is to assist water resource managers in taking the best decision and reduce risks. Other references (Crimi et al 2006) and (Khawlie 2006) discusses the data availability with respect to water In general the goal of this research paper is to discuss the process of implementing an online meta-database as part of the WP4.…”
Section: Introductionmentioning
confidence: 99%
“…One can mention references in (Ackland et al 2005) where an Australian Web-based service is suggested whose role is to assist water resource managers in taking the best decision and reduce risks. Other references (Crimi et al 2006) and (Khawlie 2006) discusses the data availability with respect to water In general the goal of this research paper is to discuss the process of implementing an online meta-database as part of the WP4.…”
Section: Introductionmentioning
confidence: 99%
“…Section 3 describes the XACML access control model and how we applied it to this problem. In Section 4 we outline the standard model for RBAC, 1 The Health Data Integration™( HDI™ ) system are trademarks of CSIRO for a system derived from the HDI system described in this paper and in the referenced literature and it has a somewhat different architecture from the version described. HDI™ was developed by the e-Health Research Centre (http://e-hrc.net.au).…”
Section: Introductionmentioning
confidence: 99%
“…The Health Data Integration™ (HDI™) project [1], [3] at CSIRO ICT Centre has been developing technology which allows the linking, integration and analysis of population-based health data held by disparate data custodians for public health research. In a climate of increasing concern for individuals' privacy and confidentiality, and in the face of a growing body of legislation and codes of practice governing the use of personal and health data, it is essential that the HDI technology have strong and flexible security and privacy safeguards 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Though Web services (WS) technology as the most commonly used implementation of traditional SOA reduces the number of point-to-point adapters because every interface is based on WS Description Language (WSDL), it still leaves open the question of semantic interoperability of these interfaces. That is why recently a major effort has been invested in semantic extensions of SOA known as Semantic SOA allowing for scalable and controlled EAI [2][3][4].…”
Section: Introductionmentioning
confidence: 99%